Scar quantification by cardiovascular magnetic resonance as an independent predictor of long-term survival in patients with ischemic heart failure treated by coronary artery bypass graft surgery. Issue 1 (December 2016) - Kancharla, Krishna; Weissman, Gaby; Elagha, Abdalla; Kancherla, Kalyan; Samineni, Swetha; Hill, Peter; Boyce, Steven; Fuisz, Anthon
Abstract Background Scar burden by late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) is associated with functional recovery after coronary artery bypass surgery (CABG). There is limited data on long-term mortality after CABG based on left ventricular (LV) scar burden. Methods Patients who underwent LGE CMR between January 2003 and February 2010 within 1 month prior to CABG were included. A standard 16 segment model was used for scar quantification. A score of 1 for no scar, 2 for ≤ 50 % and 3 for > 50 % transmurality was assigned for each segment. LV scar score (LVSS) defined as the sum of segment scores divided by 16. All-cause mortality was ascertained by social security death index. Results One hundred ninety-six patients met the inclusion criteria. 185 CMR studies were available. History of prior MI was present in 64 % and prior CABG in 5.4 % of patients. Scar was present in 72 % of patients and median LVEF was 38 %. Over a median follow up of 8.3 years, there were 64 deaths (34.6 %). There was no statistically significant difference in mortality between Scar and No-scar groups (37 % versus 29 %). In the group with scar, a lower scar burden (defined either < 4 segments with scar or based on LVSS) was independently associated with increased survival. Conclusion In patients undergoing surgical revascularization, scar burden is negatively associated with survival in patients with scar. However, there is no difference in survival based on presence or absence of scar alone. CMR prior to CABG adds additional prognostic information.